Food safety practices in childcare centers in Kansas - Fan, Shengjie (Kansas State University, 2013)
The Centers for Disease Control and Prevention estimated that one in six Americans become ill,128,000 are hospitalized, and 3,000 die each year due to foodborne illness. Children are at a higher risk of acquiring foodborne illness than adults for several reasons, including: an immune system that has yet to fully develop, limiting their ability to fight infections; a lack of control over the food they consume because their meals are usually provided by others; and the lack of awareness of food safety risks. Thus, it is critical to ensure that childcare center employees practice safe food handling. The purpose of this study was to explore the food safety knowledge, practices, and barriers to safe food handling practices of childcare center employees. Observations were conducted in 10 childcare centers in Manhattan, Kansas. Each childcare center was observed for two days during lunch preparation and service. Observations of foodservice employees were conducted in the kitchen using a structured observation form. Teacher observations were conducted in the classroom using detailed notes. A questionnaire was used to collect demographic, food safety training, and food safety knowledge information. SPSS (v. 20.0) was used to analyze data. Childcare center employees had high average scores on the safety knowledge assessment. The majority of employees received some type of food safety training. Time pressures, availability of equipment, and small food preparation space were found as the main barriers to implementing safe food handling. Childcare center foodservice workers and teachers were knowledgeable about handwashing and time/temperature control, but failed to utilize on the job. Results of this study will help childcare educators to develop materials to improve food safety practices and encourage owners/managers of childcare centers to enhance their food safety behaviors.
Keywords: Childcare; Foodborne illness; Safe food handling; Early Childhood Education (0518); Elementary Education (0524); Food Science (0359); Health Care Management (0769); Health Education (0680); Public Health (0573)